Synthesis of magnetic porous carbon composite derived from metal-organic framework using recovered terephthalic acid from polyethylene terephthalate (PET) waste bottles as organic ligand and its potential as adsorbent for antibiotic tetracycline hydrochloride - Jung, Kyung-Won; Kim, Jun-Ho; Choi, Jae-Woo (ELSEVIER SCI LTD, 2020)
The widespread overuse of antibiotics has led to the serious risks human life and environmental sustainability. Even though porous carbon composite derived from metal-organic framework (MOF) has been recognized as an efficient adsorbent for sequestering antibiotics owing to its unique properties, the major drawback is the use of the expensive material, such as terephthalic acid (H2BDC), as an organic ligand, thus weakening its cost effectiveness and practical applicability. Herein, we successfully recovered H2BDC from polyethylene terephthalate (PET) waste bottles via ultrasound-assisted, phase-transfer-catalyzed alkaline hydrolysis under mild conditions. The process conditions were statistically optimized by applying response surface methodology (RSM) based on the Box-Behnken design. As results, 99.91-100% H2BDC recovery was achieved under the following optimized conditions: NaOH concentration = 14.5%; temperature = 83.2 degrees C; and time = 1.5 h. High-purity H2BDC was used as an organic ligand in the synthesis of magnetic porous carbon (alpha-Fe/Fe3C) composite derived from iron-based MOF, and its utilization as an adsorbent for the removal of TCH from aqueous solution was investigated. The as-prepared alpha-Fe/Fe3C composite comprised alpha-Fe, Fe3C, and graphitic carbon and exhibited mesoporous structure and superparamagnetic behavior, resulting in an effective adsorption performance and magnetic separation. Its adsorption properties were examined in terms of solution pH, contact time, initial TCH concentration, and temperature. Adsorption kinetics and isotherm data were well-suited to the pseudo-second-order and Langmuir models, respectively. Considering its excellent reusability and magnetic separability, the alpha-Fe/Fe3C composite showed immense potential for antibiotic-contaminated wastewater remediation.